Instability in Indian food grain production - "Hazell, Peter B.R." (Washington, 1982)
The last three decades have seen Indian's total cereal production grow significantly, by, on average about 2.7 percent per year. Average production increased by 44 percent (or 29.4 million tons) between the periods 1954/55-1964/65 and 1967/68-1977/78. Almost half of this was due to a remarkable increase of 142 percent in wheat production (14.4 million tons) and one third was due to a 32 percent increase in rice production (10.3 million tons).
Keywords: Grain trade India